2021
DOI: 10.1177/09636897211067804
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Clinical Efficacy of Stem Cell Transplantation in the Treatment of Spinal Cord Injury: A Systematic Review and Meta-analysis

Abstract: Stem cell transplantation has been applied to treat spinal cord injury (SCI) in clinical trials for many years. However, the clinical efficacies of stem cell transplantation in SCI have been quite diverse. The purpose of our study was to systematically investigate the efficacy of stem cell transplantation in patients with SCI. The PubMed, Web of Science, Ovid-Medline, Cochrane Library, China National Knowledge Infrastructure, VIP, Wanfang, and SinoMed databases were searched until October 27, 2020. Quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Tang, Q. R. et al. mentioned the pain, fever, and headache as the most common mild and moderate AEs in stem cell transplantation for treatment of spinal cord injury [ 54 ]. The most reported AEs were febrile reaction, headache, and neurologic pain with mild or moderate severity in ten studies in Liu, S. et al.…”
Section: Discussionmentioning
confidence: 99%
“…Tang, Q. R. et al. mentioned the pain, fever, and headache as the most common mild and moderate AEs in stem cell transplantation for treatment of spinal cord injury [ 54 ]. The most reported AEs were febrile reaction, headache, and neurologic pain with mild or moderate severity in ten studies in Liu, S. et al.…”
Section: Discussionmentioning
confidence: 99%
“…In order to better highlight the purpose and value of this study, we compared it with previously published studies. A total of 8 systematic reviews/meta-analyses (SR/MA) of stem cells for SCI were searched [ 20 , 21 , 109 114 ], as detailed in Table 2 . Although safety is paramount for the clinical application of any therapy, we found that the published SR/MA focused on efficacy indicators while largely ignoring the safety outcomes of stem cell therapy.…”
Section: Similarities and Differences With Similar Studiesmentioning
confidence: 99%
“…2) More adverse effects occurred after stem cell transplantation, mainly including fever (7.59%), headache (5.69%), and neuropathic pain (4.88%). Tang et al [ 20 ] Meta-analysis of head-to-head comparisons 9 328 3 ASIA impairment scale grade; urodynamic indices 1) Compared with conventional treatment, stem cells can significantly improve ASIA and improve bladder function. 2) More AEs occurred after stem cell transplantation, mainly including neuropathic pain (RR = 1.58, 95%CI [0.92, 2.72], p = 0.10), fever (RR = 4.22, 95%CI [1.74, 10.22], p = 0.001), and headache (RR = 2.40, 95%CI [0.57, 10.17], p = 0.23).…”
Section: Similarities and Differences With Similar Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal Stem Cells or Mesenchymal Stromal Cells (MSCs) are multipotent progenitor cells, which exhibit the greatest potential for treating spinal cord injury among all stem cell types [7]. Several types of stem cells have been tested or being tested clinically for the treatment of SCI, including MSCs, ESC-derived oligodendrocytes precursor cells, fetal-derived neural stem cells, and central nervous system stem cells [8]. Most of the trials used MSCs isolated from bone marrow (BMSCs), umbilical cord (UC-MSCs) and adipose tissue (ADSCs) to treat SCI [9].…”
Section: Introductionmentioning
confidence: 99%